The influence of stress on the occurrence of bruxism - Martyna Nowińska; Magdalena Kozyra; Patryk Zimnicki; Justyna Kaczerska; Natalia Śmiech; Joanna Milanowska (Kazimierz Wielki University, 2020)
Introduction: Bruxism is defined as a stereotypical hyperactivity of the masseter characterized by clenching and grinding of the teeth. Etiopathology of bruxism still remains unclear, is one of the least known dysfunctions of the stomatognathic system. However, a lot of research have shown the correlation between stress and bruxism. The aim of the study: Paying attention to the correlation between the occurrence of stress and the presence of bruxism in the population. Material and method: The research was done by the usage of the PubMed and Google Scholar articles about the topic of: bruxism; stress; epidemiology; characteristic; psychotherapy; Description of the state of knowledge: Psychosocial factors such as state anxiety and trait anxiety, alexithymia, and perceived stress are as important as somatic causes in the occurrence and maintenance of bruxism. Impact of stress is especially noticeable during research conducted on students. Management of bruxism should embrace dental, pharmacological and psychobehavioural procedures. It requires a wider analysis in the aspect of concomitant disorders. The involvement of different specialists is required. Summary: We can undoubtedly say that stress is an inherent condition that accompanies us in everyday life. However, it is important to pay attention to its coexistence with bruxism and its harmful effect not only on organs such as the heart or stomach, but also the stomatognathic system - which is confirmed by many studies. However, the multidimensionality and complexity of the etiology of bruxism require further considerations and research.